2019
DOI: 10.1002/anie.201812902
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Lifetime of Native GTP‐Bound Ras for Site‐Resolved NMR Measurements: Quantifying the Allosteric Dynamics

Abstract: Characterization of native GTP‐bound Ras is important for an appreciation of its cellular signaling and for the design of inhibitors, which however has been depressed by its intrinsic instability. Herein, an effective approach for extending the lifetime of Ras⋅GTP samples by exploiting the active role of Son of Sevenless (Sos) is demonstrated that sustains the activated state of Ras. This approach, combined with a postprocessing method that suppresses residual Ras⋅GDP signals, is applied to the site‐resolved N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 40 publications
3
47
0
Order By: Relevance
“…This protocol did not require the use of any other added protein as the method was published recently. 16 NMR measurements were performed at 298 K on a Bruker Avance III 700 MHz spectrometer equipped with a 5 mm Prodigy TCI H&F-C/N-D, z-gradient probe head operating at 700.05 MHz for 1 H-, 70.94 MHz for 15 N-and 176.03 MHz for 13 C-nuclei. Temperature was calibrated using a standard methanol solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol did not require the use of any other added protein as the method was published recently. 16 NMR measurements were performed at 298 K on a Bruker Avance III 700 MHz spectrometer equipped with a 5 mm Prodigy TCI H&F-C/N-D, z-gradient probe head operating at 700.05 MHz for 1 H-, 70.94 MHz for 15 N-and 176.03 MHz for 13 C-nuclei. Temperature was calibrated using a standard methanol solution.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15] In a recent study, to avoid this problem, GEF protein (SOS) was added to the native HRAS-GTP NMR sample. 16 However, since GEF displaces the switch I region in its entirety (by over 10Å) and remodels switch II 17 even if it is added to the samples in minimal amountsthe results thus derived might be altered from the RAS-GTP native state. These limitations prevent clarifying what steps constitute the transition to the active form, which features of the activated state are recognized by the downstream partners and the conformational criteria of inactivationthus, the exact mechanism of the rise and shutdown of the growth signal.…”
Section: Introductionmentioning
confidence: 99%
“…The authors assigned the lower populated conformational state to state 1 of Ras-GTP by comparing the obtained chemical shift differences for backbone N-atoms with those of Ras-Thr35Ala-GTP in very good agreement. They also found that the residues mostly affected in the state 1 ↔ state 2 slow motions are found in the effector lobe and the α3 helix of the allosteric lobe [31].…”
Section: The Overall Ras Conformational Ensemblementioning
confidence: 95%
“…The effector and nucleotide-binding sites of the effector lobe partially overlap, located on opposing sides of the segment named switch I (residues [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Further regions participating in hosting the nucleotide are the phosphate-binding Ploop (residues 10-17) and switch II (residues 57-76) of the effector lobe [7,9] and the nucleobase binding-loops of the allosteric lobe (residues 116-120 and 145-147) [7].…”
Section: Ras Proteins: Structure Dynamics and Functionmentioning
confidence: 99%
See 1 more Smart Citation